2021
DOI: 10.1007/s40519-021-01173-w
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal obesity phenotype is associated with COVID-19 chest X-ray severity score better than BMI-based obesity

Abstract: Purpose Chest X-ray (CXR) severity score and BMI-based obesity are predictive risk factors for COVID-19 hospital admission. However, the relationship between abdominal obesity and CXR severity score has not yet been fully explored. Methods This retrospective cohort study analyzed the association of different adiposity indexes, including waist circumference and body mass index (BMI), with CXR severity score in 215 hospitalized patients with COVID-19. Resul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 58 publications
1
7
0
1
Order By: Relevance
“…In our study, WC showed a strong association with intensive ventilatory support. In line with our findings, Malavazos et al and Van Zelst and colleagues found that central obesity measured through WC was the best predictor for the radiological severity of disease and negative outcome, respectively [29,30]. Advocated as a vital sign in clinical practice, the measurement of WC is a simple, inexpensive, bedside and easily standardizable method that is considered important for risk stratification [28].…”
Section: Discussionsupporting
confidence: 88%
“…In our study, WC showed a strong association with intensive ventilatory support. In line with our findings, Malavazos et al and Van Zelst and colleagues found that central obesity measured through WC was the best predictor for the radiological severity of disease and negative outcome, respectively [29,30]. Advocated as a vital sign in clinical practice, the measurement of WC is a simple, inexpensive, bedside and easily standardizable method that is considered important for risk stratification [28].…”
Section: Discussionsupporting
confidence: 88%
“…A study found that abdominal obesity was associated with a high chest x-ray severity score better than BMI. [24] UK study found that high WC was associated with positive COVID-19 test only in people > 65 years, independent of BMI. [25] Another study found a positive association between WC and COVID-19 susceptibility (OR = 1.38; 95% CI: 1.07-1.78; p=0.015).…”
Section: Characteristics Of the Study Subjectsmentioning
confidence: 89%
“…Clinical studies on abdominal obesity and COVID-19 are still evolving. One study found that abdominal obesity was associated with a high chest x-ray severity score better than BMI [ 33 ]. A UK study found that high WC was associated with a positive test for the SARS-CoV-2 virus only in people ≥ 65 years, independent of BMI [ 34 ].…”
Section: Discussionmentioning
confidence: 99%